2007
DOI: 10.1302/0301-620x.89b7.18980
|View full text |Cite
|
Sign up to set email alerts
|

Locally administered low-dose alendronate increases bone mineral density during distraction osteogenesis in a rabbit model

Abstract: We investigated the effect of locally administered bisphosphonate on distraction osteogenesis in a rabbit model and evaluated its systemic effect. An osteotomy on the right tibia followed by distraction for four weeks was performed on 47 immature rabbits. They were divided into seven equal groups, with each group receiving a different treatment regime. Saline and three types of dosage of alendronate (low, 0.75 microg/kg; mid, 7.5 microg/kg and high 75 microg/kg) were given by systemic injection in four groups,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 29 publications
3
21
0
4
Order By: Relevance
“…[22][23][24] In an animal model of distraction osteogenesis, a low dose is more effective than a mid dose local use of alendronate in preserving the BMC of the lengthened segments; higher doses of alendronate could lead to inhibition of osteoblasts and therefore affect outcomes adversely. 17 In our study, low-dose continuous local injection of risedronate increased both BMC and BMD of the newly formed bone segments and prevented osteoporosis in the bone regions proximal and distal to the lengthened segments. The BMC of the lengthened segments was 65% higher in the risedronate group, as was in the segments proximal and distal to the regenerate bone (31% and 21%, respectively).…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…[22][23][24] In an animal model of distraction osteogenesis, a low dose is more effective than a mid dose local use of alendronate in preserving the BMC of the lengthened segments; higher doses of alendronate could lead to inhibition of osteoblasts and therefore affect outcomes adversely. 17 In our study, low-dose continuous local injection of risedronate increased both BMC and BMD of the newly formed bone segments and prevented osteoporosis in the bone regions proximal and distal to the lengthened segments. The BMC of the lengthened segments was 65% higher in the risedronate group, as was in the segments proximal and distal to the regenerate bone (31% and 21%, respectively).…”
Section: Discussionsupporting
confidence: 56%
“…5 Low-dose injection to the distraction site diminishes the chance of systemic drug dispersion. Recent in vitro and in vivo studies are all in favour of low drug concentrations 17,[22][23][24] ; low-dose N-BPs are capable of inhibiting bone resorption (by osteoclasts) and stimulating osteoblasts, which in turn promotes new bone formation. Conversely, higher doses of N-BPs may result in osteoblast inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This and earlier (Wilkinson & Little 2011) studies further add a possibility that local application of N-BPs may be useful for local bone augmentation. It has been reported that locally administered ALN increased bone mineral density in a rabbit model (Omi et al 2007). Surface coatings of zoledronate and pamidronate have also been reported to cause bone increase around orthopedic implants in animal models (Tanzer et al 2005, Wermelin et al 2008, Gao et al 2009).…”
Section: K6mentioning
confidence: 99%